PERAN MOTIVATOR DINAS PARIWISATA DALAM PENGEMBANGAN WISATA INDUSTRI DI KABUPATEN BEKASI - Fraya Diaz Rasyade; Hanny Purnamasari; Rachmat Ramdani (LPPM Universitas Abdurrab, 2025)
Tourism serves as an important economic driver that provides great benefits to the country and society. Indonesian Tourism Law No. 9 of 2009 aims to increase economic growth and preserve nature and culture. This study uses a qualitative method to explore more deeply the role of the Tourism Office in Industrial Tourism in Bekasi Regency. Using one of the indicators according to Pitana and Gayatri (2005, 95 in Deki, 2019), namely the role of the Tourism Office as a motivator. As a result, as a strategic industrial center in Bekasi Regency, which houses more than 7,000 factories, it presents opportunities for industrial tourism to boost the local economy. The appeal of industrial tourism includes the unique and educational experiences it offers, with factory visits guided by professionals. Since 2010, the Bekasi Regency Tourism Office has faced challenges in promoting industrial tourism effectively, thus requiring continuous evaluation and improvement of promotional strategies. Although lacking in natural tourist attractions, the potential for industrial tourism that stands out in Bekasi Regency deserves attention. The government must strengthen its motivational role by utilizing social media and outreach programs to reach a wider audience, thereby increasing tourist interest and regional income.